Development of a miniaturized Ti-plasmid and helper plasmid system for Agrobacterium-mediated plant transformation - Yuh, Leng Teo; Shu, Ting Chang; Wai, Keat Toh; Xin, Yen Tor; Chai, Ling Ho; Pek, Chin Loh; Hann, Ling Wong (Malaysian Society of Molecular Biology and Biotechnology, 2023)
Tumor-inducing (Ti) plasmid is the requisite for Agrobacterium-mediated plant transformation. Over decades, continuous efforts have been made to improve the efficiency of Agrobacterium-mediated plant transformation and most of them focused on the binary vector system. A binary vector system comprises of a binary vector of which transferred DNA (T-DNA) resided on and a Ti plasmid to carry those essential virulence genes. In this study, we constructed a miniaturized helper Ti plasmid, designated as pYL102, with the aim to enhance the overall Agrobacterium-mediated transformation rate. The size of pYL102 was reduced to ~60% of the original plasmid pCAMBIA5105. Subsequently, pYL102 was coupled with the broad host range (BHR) bacterial expression vector, pYL101C, of which the key regulatory virulence gene, virG-N54D, was cloned in and expressed under the control of a strong constitutive PINTc promoter. To test the functionality of the constructed vector system, A. tumefaciens C58C1 carrying pYL102, pYL101C::virG-N54D and the transformation vector pGWB2::e35S-sfGFP was used to transform Nicotiana benthamiana leaves by agroinfiltration. Green fluorescence was observed in spots infiltrated with Agrobacterium carrying the test plasmids. The fluorescence intensity from the test agroinfiltrated leaves was significantly higher than those of the mock-infiltrated leaves (p<0.01), indicating the vector system can be used for plant transformation.